Audit Tata Kelola Sistem Informasi Manajemen Kepegawaian Perguruan Tinggi dan Proses Investasinya Menggunakan Framework Cobit - Rifan Romadon; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
POLBAN has implemented a Personnel Management Information System which is used to assist management in managing, monitoring and recapitulating personnel data reports. However, the IT governance process is still not optimal and there are still many shortcomings. The purpose of this research is to know the processes and procedures for the management of SIMPEG POLBAN, IT Risk, IT Control, IT investment processes and measurement maturity levels of IT Governanceusing COBIT 4.1.measurement is Maturity level based on four domains in COBIT, namely Planning and Organize, Acquire and Implementation, Delivery and Support, and Monitor and Evaluate. The results of research conducted at SIMPEG POLBAN, obtained a level of maturity at level 2, namely Repeatable but Intuitive. This means that IT activities are still carried out according to custom without any clearly written procedures. The results of measuring the level of maturity are expected to become input in POLBAN's future strategic development plans.